Julian Disney address at the National Press Club on 23 October 1991 - Disney, Julian; National Press Club (Australia) (1991)
Disney discusses the economic and social consequences of the recession; the faults of current economic policies, and suggests measures to help Australia back to economic prosperity.
Also available online
Transcript available (typescript, 17 leaves) titled: Advance Australia Fair? Recession, recovery and social justice.
Keywords: Disney, Julian; Australia -- Economic conditions -- 1990-2001.; Australia -- Economic policy -- 1990-2001.; Australia -- Social conditions -- 1990-2001.